Impact of mode of conception on early pregnancy human chorionic gonadotropin rise and birth weight - Hayley Richardson, M.S; Charikleia Kalliora, M.D., M.Sc; Monica Mainigi, M.D; Christos Coutifaris, M.D., Ph.D; Mary D. Sammel, Sc.D; Suneeta Senapati, M.D, M.S.C.E (Elsevier, 2022)
Objective: To assess whether the mode of conception and embryo biopsy impact first-trimester human chorionic gonadotropin (hCG) dynamics and subsequent risk of small for gestational age (SGA) or large for gestational age (LGA). Design: Retrospective cohort study. Setting: University fertility center. Patient(s): Six hundred-two pregnant patients with singleton live births. Intervention(s): Serial serum hCG measurements were obtained between 10 and 28 days postconception to determine the within-woman rate of change in hCG (slope) by mode of conception (unassisted pregnancy, fresh embryo transfer (ET), frozen ET, and frozen ET following preimplantation genetic testing for aneuploidy (PGT-A). Main Outcome Measure(s): Primary outcomes included birth weight, SGA, and LGA. Result(s): Mode of conception is not independently associated with birth weight, SGA, or LGA. Mediation analysis revealed an expected one-day increase in log-transformed hCG varied by mode of conception: unassisted (0.41), fresh ET (0.39), frozen ET (0.42), PGT-A (0.44). Human chorionic gonadotropin rise has a positive effect on birth weight (55 g per SD increase in hCG slope) and is associated with SGA (odds ratio, 0.65), but not with LGA (odds ratio, 1.18). Conclusion(s): Human chorionic gonadotropin rise is an important mediator of the mode of conception/birth weight relationship. Preimplantation genetic testing for aneuploidy has the highest rate of hCG rise, followed by frozen ET, unassisted, and fresh ET. Faster rise is associated with higher birth weight and lower risk of SGA but does not impact LGA risk. Importantly, PGT-A does not increase the risk of extreme birth weight relative to other modes of conception evaluated.